The Philippine Muslims: Our Link to Southeast Asia - Sakili, Abraham P. (Kasarinlan: Philippine Journal of Third World Studies; Vol 15 No 2 (2000): Indigenous Peoples, 2008)
Pre-colonial Philippine culture was greatly enriched through trade relations with its neighbors in Southeast Asia. In the southern islands of Islamized Mindanao emerged sultanates which had extensive ties with the region and the Muslim world beyond. When Europe took possession of Southeast Asia and its vast natural resources, the Dutch, British and French opted to leave cultures alone, allowing future generations to retain their way of life. In the Philippines, the Spaniards did otherwise, Catholicizing whatever was within reach. The Muslims of Mindanao resisted and having survived, saved their culture from disintegration and preserved the country's only link with the rest of Southeast Asia.
Keywords: Philippine Muslims; Philippine Moro; Islam